Effects of feed particle size on caecal activity and growth performances in fattening rabbits - Lambertini, L.; Vignola, G.; Dainese, E.; Cipollini, I. (Progress in Nutrition, 2007)
Aim of this work was to investigate the effects of particle size of feeds for fattening rabbits on growth performances, slaughtering data and, particularly, on their caecal fibrolytic activity and caecal content characteristics. 72 hybrid commercial rabbits 40 days old, divided in two experimental groups, were fed to slaughter (88 days) two pelletted diets (F – fine; C – coarse) of similar composition differing only in the grinding level of dehydrated lucerne meal and wheat bran. 42.3% of diet F was composed by particles with Æ